Caractérisation des plaques d'identification militaires en zinc provenant du site de Carspach (Alsace, Haut-Rhin, F) - Marie-Jeanne Scholl (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The excavation of the shelter « Kilian » in Carspach (Haut-Rhin, F), allowed to study the behavior of modern metals in archaeological context, through the example of military identification tags made of zinc. Ensure long-term preservation of the tags, and thus their meanings, requires understanding the mechanisms of corrosion of archaeological zinc, including assessing the stability of the current state of conservation. This thesis reports the diagnostic examination of these objects, including a thorough description of corrosion achieved from macro and microscopic observations and physicochemical analysis (XRF, SEM-EDX, FTIR and Raman) and propose a methodology to help the choice of a treatment protocol, adapted to this type of objects.